Identifikasi Kesalahan Teknik Smash Bola Voli Klub Meteor Pontianak - Eka Supriatna; Oviesta Tasha Retyananda; Isti Dwi Puspitawati (Universitas Negeri Padang, 2021)
The research motivated by the problem of lack of correction in the volleyball smash technique. This study aims to identify the errors of the Pontianak meteor club volleyball player smash technique. Thi research was a descriptive percentage. The method used was a survey with an observation sheets, field observations, and documentation. The sample in this study consisted of 11 athletes who have the criteria: (1) athlete were present at the time of data collection, (2) athlete who has a specialist as a speaker. The data analysis technique used a descriptive analysis which an stated in the form of a percentage. The results showed that there was an error volleyball smash technique in: (1) the initial stage was 25.39%, (2) the repulsion / jump stage was 25.37%, (3) the hitting stage was 25.42% and, (4) when landing is 23.82%. So it can be concluded that the landing stage has the largest percentage of errors.